Consumer factors associated with purchasing local versus global value chain foods. Issue 1 (3rd November 2016) - Bogomolova, Svetlana; Loch, Adam; Lockshin, Larry; Buckley, Jon
Abstract: Global value chains (GVCs) have grown to represent the major source of modern food and grocery items. Yet there is an increasing preference among consumers toward locally sourced and supplied foods among perceptions of health, economic and community benefits. Typically purchased in farmers' markets and specialty outlets, local foods are becoming more widely available in supermarkets, who are now interested in how they might introduce or increase that product range. We collect actual purchase data from a regional supermarket chain and analyze the drivers of higher local food proportional outcomes across a sample of consumers. Attempts to link theoretically important drivers of local food purchasing in traditional (e.g., farmers' market) outlets to supermarket settings proved difficult. Results do, however, suggest some means by which parties interested in developing local value chains between regional suppliers and supermarket outlets could be achieved. As such, the study is a useful first-step in the development of new value chains to address future potential issues of socio-economic stratification and inequality as a consequence of GVC prevalence.